The Last Mile : Delivery Mechanisms for Post-Disaster Finance - Hallegatte, Stephane; Rentschler, Jun (World Bank, Washington, DC, 2018)
Governments now have access to a large and growing range of financing instruments for rapidlymobilizing funds in the aftermath of a disaster. Instruments like reserve funds, contingent linesof credit, and insurance programs are critical for financing relief, recovery and reconstruction efforts, and they have a demonstrated impact on the ability of governments to manage large-scale disasters. The availability of financial resources however, is only half of the story. The capacity of a government to support post-disaster recovery and reconstruction depends substantially on its ability to deliver these resources effectively to where they are needed. Doingso requires that governments are prepared before a disaster hits, with the right instruments, institutions, and capacities in place. By preparing contingency plans, defining responsibilities, adopting appropriate regulations and norms, enhancing financial inclusion and insurance regulations, and establishing flexible and gender-inclusive social protection systems, governments could improve the reconstruction process and generate over 173 billion dollars per year inbenefits. There are major synergies between the financial instruments that make the resources available and the systems that deliver these resources where they are needed. In the next few years, the design and implementation of new financial instruments will offer an unprecedented opportunity to improve the last-mile delivery of post-disaster support. This opportunity should not be missed.